Seroprevalence of Leptospira interrogans infection in horses from some horse clubs in Tehran by Microscopic Agglutination Test (MAT) - mohammadrahim Haji Hajikolaei; alireza Nafisi Mozaffar; samad Lotfollazadeh; masoud Ghorbanpour; gholamreza Abdollapour (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2016)
In order to evaluate the seroprevalence of Leptospira interrogans infection in horses, blood samples were taken from 152 horses from 7 horse clubs in Tehran. Serum samples were examined using a microscopic agglutination test to detect the presence of antibodies against five live serotypes of Leptospira interrogans (grippotyphosa, pomona, icterohaemorrhagiae, canicula and hardjo). Of the tested samples, 23 horses (15/13%) were positive to one or more serotypes. Titer levels ranged from 1:100 to 1:200. Icterohaemorrhagiae (44/44%) was the most frequently detected serovar followed in descending order by gripotyphosa (29/62%), canicula (22/22%), pomona (3/7%) and serotype hardjo was negative. Statistical analysis using the chi-squared test showed there was no significant correlation differences between Leptospira interrogans infection and factors such as sex and age. The serum titers of infected horses ranged from 1:100 (n=19) to 1:200 (n=78). These results suggest that the icterohaemorrhagiae serovar may be the most prevalent serovar in the horse population Tehran.